Clinical management of elbow hygroma in a Malayan Tigress (Panthera tigris jacksoni): a case report - Kamaruddin, Zubaidah; Chong, Chiu Nie; Hambali, Idris Umar; Abdullah Jesse, Faez Firdaus; Wan Jaafar, Wan Nor Fitri; Lim, Eric Teik Chung; Abba, Yusuf; Bitrus, Asinamai Athliamai; Peter, Innocent Damudu; Paul, Bura Thlama; Selamat, Siti Suzana; Hassan, Hasdi; et al. (Nexus Academic Publishers, 2020)
This case reports detail the clinical management of an elbow hygroma in a Malayan Tigress (Panthera tigris jacksoni). A twelve (12) years old Malayan Tigress weighing 112 kg with body condition score of 3/5 kept in captivity was reported by rangers in the National Wildlife Rescue Centre, Sungkai, Perak, Malaysia with a primary complaint of a lump at the right elbow of the forelimb. Physical and clinical examinations showed normal pulse and respiratory rates, additionally, an 8 cm x 9 cm well demarcated, soft lump caudal to the right forelimb elbow joint was palpated. Based on the physical examination and clinical signs, a diagnosis of elbow hygroma was made on that point of time. The tigress was managed by surgical lancing and wound cleaning. During the intra-operative session, the tigress was premedicated with an anti-cholinergic agent, an antibiotic, an anti-inflammatory agent and a supplement of vitamin D. During the post-operative medical management, antibiotic was administered to prevent secondary bacterial infection, papase as anti-inflammatory and iodine spray for wound care management. In conclusion, hygroma on the elbow was managed non-invasive surgical procedure and proper management by avoiding the overwhelming effects of possible risk factors can be a preventive measure for this case.